Differentially Regulated Host Proteins Associated with Chronic Rhinosinusitis Are Correlated with the Sinonasal Microbiome - Biswas, Kristi; Wagner Mackenzie, Brett; Waldvogel-Thurlow, Sharon; Middleditch, Martin; Jullig, Mia; Zoing, Melissa; Taylor, Michael W.; Douglas, Richard G. (Frontiers in Cellular and Infection Microbiology, 2017)
The chronic inflammatory nature of chronic rhinosinusitis (CRS) makes it a morbid condition for individuals with the disease and one whose pathogenesis is poorly understood. To date, proteomic approaches have been applied successfully in a handful of CRS studies. In this study we use a multifaceted approach, including proteomics (iTRAQ labelling) and microbiome (bacterial 16S rRNA gene sequencing) analyses of middle meatus swabs, as well as immune cell analysis of the underlying tissue, to investigate the host-microbe interaction in individuals with CRS (n = 10) and healthy controls (n = 9). Of the total 606 proteins identified in this study, seven were significantly (p < 0.05) more abundant and 104 were significantly lower in the CRS cohort compared with healthy controls. The majority of detected proteins (82% of proteins identified) were not significantly correlated with disease status. Elevated levels of blood and immune cell proteins in the CRS cohort, together with significantly higher numbers of B-cells and macrophages in the underlying tissue, confirmed the inflammatory status of CRS individuals. Protein PRRC2C and Ras-related protein (RAB14) (two of the seven elevated proteins) showed the biggest fold difference between the healthy and CRS groups. Validation of the elevated levels of these two proteins in CRS samples was provided by immunohistochemistry. Members of the bacterial community in the two study cohorts were not associated with PRRC2C, however members of the genus Moraxella did correlate with RAB14 (p < 0.0001, rho = - 0.95), which is a protein involved in the development of basement membrane. In addition, significant correlations between certain members of the CRS bacterial community and 33 lower abundant proteins in the CRS cohort were identified. Members of the genera Streptococcus, Haemophilus and Veillonella were strongly correlated with CRS and were significantly associated with a number of proteins with varying functions. The results from this study reveal a strong association between the host and microbes in the sinonasal cavity. Proteins identified as associated with CRS could be new targets for drug therapies and biomarkers for assessment of treatment efficacy.